2012
DOI: 10.2147/ijn.s37650
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the oral bioavailability of poorly water-soluble carbamazepine using immediate-release pellets supported on SBA-15 mesoporous silica

Abstract: Background and methods:The aim of this study was to develop an immediate-release pellet formulation with improved drug dissolution and adsorption. Carbamazepine, a poorly watersoluble drug, was adsorbed into mesoporous silica (SBA-15-CBZ) via a wetness impregnation method and then processed by extrusion/spheronization into pellets. Physicochemical characterization of the preparation was carried out by scanning electron microscopy, transmission electron microscopy, nitrogen adsorption, small-angle and wide-angl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 35 publications
(35 reference statements)
1
14
0
Order By: Relevance
“…2d). These results verified the typical two-dimensional structure of the material (Wang et al, 2012). For SBA-16 the mean pore size was about 6 nm (measured from the images).…”
Section: Resultssupporting
confidence: 84%
“…2d). These results verified the typical two-dimensional structure of the material (Wang et al, 2012). For SBA-16 the mean pore size was about 6 nm (measured from the images).…”
Section: Resultssupporting
confidence: 84%
“…For the CIP-loaded MCM-41 sample the broad halo in the range of 15-35° derived from the amorphous silica with significant reduction of peaks characteristic for the CIP. Two diffraction peaks at 8 and 27° 2 Ξ observed in CIP-loaded MCM-41 sample suggested the semi-crystalline nature of CIP molecules adsorbed onto the silica surface [38]. In the case of both the F3 and MCM-F3 the XRD patterns showed two broad amorphous halos at 10-15° and 15-30° 2 Ξ which clearly revealed the amorphous nature of the obtained films.…”
Section: Resultsmentioning
confidence: 97%
“… 38 All the above mentioned structural characteristics indicated that synthetic MSn was suitable as an oral drug delivery carrier the same as other mesoporous materials. 39 , 40 …”
Section: Resultsmentioning
confidence: 99%